Pegaruh Kepemimpinan Berdasarkan Nilai Keislaman (Sifat Tauladan Muhammad SAW) Terhadap Kinerja Karyawan - Rina Hastuti; Septi Kurnia Prastiwi (EBBANK, 2017)
The aim of this research is to test the relationship between islamic spiritual intelligence and  employee spiritual value toward employee performance. To strengthen the effect, mediating variable of employee engagement were added to the model. The research collected the data from the employee of small medium enterprise in cullinary industry which owned by  moslem entrepreneurs in Surakarta. by conduct a path analysis the research reveal that the characters of sidiq, amanah, and fatanah are significantly influence the employee spiritual value. However, the quality of Islamic leadership style is able to increase and empower the employee’s spirit value in order to achieve higer employee performance.